Cluster Analysis Use for Estimation of Telecommunications Network Quality - Gudonavicius, R.; Jankuniene, R.; Saferis, V. (Elektronika ir Elektrotechnika, 1999)
The estimation of telecommunication network is based on analytical model by using cluster analysis method. This article presents the results of network states clusterization according to measured quality parameters.